Voxel-based modeling of airflow in the human nasal cavity. Issue 3 (17th February 2019) - Kimura, Shinya; Sakamoto, Takashi; Sera, Toshihiro; Yokota, Hideo; Ono, Kenji; Doorly, Denis J.; Schroter, Robert C.; Tanaka, Gaku
Abstract: This paper describes the simulation of airflow in human nasal airways using voxel-based modeling characterized by robust, automatic, and objective grid generation. Computed tomography scans of a healthy adult nose are used to reconstruct 3D virtual models of the nasal airways. Voxel-based simulations of restful inspiratory flow are then performed using various mesh sizes to determine the level of granularity required to adequately resolve the airflow. For meshes with close voxel spacings, the model successfully reconstructs the nasal structure and predicts the overall pressure drop through the nasal cavity.